Analisis Kinerja Kemandirian Keuangan Dan Aktivitas Layanan Rawat Inap Utama Pada Badan Layanan Umum Daerah Rumah Sakit Jiwa Menur Dengan Metode Activity Based Costing - Puspitawati, Dwi Indah (Program Doktor Ilmu Ekonomi, 2014)
Background : As the Government Hospital of East Java Province, Menur Mental Hospital provide inpatient main public services with tariff that set by the Director of the hospital. Status of Badan Layanan Umum Daerah (BLUD) requires hospitals to improve financial independence along with improved quality of service, so that the necessary cost analysis as the basis for calculating rates and cost efficiency in order to make the right and accurate decisions. Determination of the major inpatient services rates using Activity Based Costing will track activity based on those costs. Objective: Calculate the unit cost per class, analyze the activity and performance of financial independence of the main inpatient services. Methods : The study design applied in a descriptive cross-sectional field.Results : The unit cost per day of hospitalization after activity analysis, are: VIP 1 Rp1.264.940,29; VIP 2 Rp982.913,63; Main 1 Rp513.692,85; Main 2 Rp423.506,13, and Main 3 Rp282.026,07. Fixed cost are Rp1.490.013.692,04; while the variable cost per class are 1 VIP Rp257.777,48; VIP 2 Rp229.777,48; Main 1 Rp195.582,48; Main 2 Rp164.852,48; and Main 3 Rp126.125,33.Conclusion : Unit Cost of all classes of treatment before analysis of activityÂ are higher than current tariff. Non value-added activities cost are Rp341.235.192,80; so that the unit cost of each class is reduced by an average 9.25% when including the salaries of civil servants, and 12.47% without the salaries of civil servants. Level of financial independence after the analysis of activity increased to 94.88% Â from 80,00% if the salaries of civil servants still subsidized by the government. Suggestion : Keep the understanding and commitment, especially in cost efficiency through further analysis of activities. If civil servants salaries are not subsidizied anymore, Main 2 and Main 3 class are not able to reach the Break Even Point (BEP), although with Bed Occupancy Rate (BOR) to be considered for a 100% rate increase.Â Keywords : Activity Based Costing, financial independence, hospital